2020
DOI: 10.3390/ijms21217904
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2/Renin–Angiotensin System: Deciphering the Clues for a Couple with Potentially Harmful Effects on Skeletal Muscle

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV-2) has produced significant health emergencies worldwide, resulting in the declaration by the World Health Organization of the coronavirus disease 2019 (COVID-19) pandemic. Acute respiratory syndrome seems to be the most common manifestation of COVID-19. A high proportion of patients require intensive care unit admission and mechanical ventilation (MV) to survive. It has been well established that angiotensin-converting enzyme type 2 (ACE2) is the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 118 publications
0
39
1
6
Order By: Relevance
“…Thus, our findings further highlight the need for clinicians to pay close attention to COVID-19 patients with elevated serum IL-6 levels at hospital admission, especially those with coexisting MAFLD. Moreover, similar to liver, it is commonly to see COVID-19 affects the skeletal muscle such as loss of muscle mass, strength, and physical function ( 33 ). Skeletal muscle is also an essential source of IL-6 ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings further highlight the need for clinicians to pay close attention to COVID-19 patients with elevated serum IL-6 levels at hospital admission, especially those with coexisting MAFLD. Moreover, similar to liver, it is commonly to see COVID-19 affects the skeletal muscle such as loss of muscle mass, strength, and physical function ( 33 ). Skeletal muscle is also an essential source of IL-6 ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is explained by up-regulation of the renin–angiotensin signaling pathway as a major mediator of feedback signaling from lowered resistance in the systemic vasculature to drive cardiac enlargement and hypercontractility [ 41 ]. Thus, although overactivity of skeletal myocyte KATP channels might contribute to atrophy, ACE/Ang II/ATR1 signaling is also a known mediator of atrophy and sarcopenia in skeletal muscle [ 42 ] and a potential major driver of the muscle pathology. Similarly, fiber damage may result in fluid leakage into the extracellular space, but the nature of the observed fluid, combined with the demonstration that lymphatic contractility can be markedly reduced by KATP GOF in lymphatic smooth muscle [ 43 ], further suggests a non-skeletal myocyte, i.e., lymphatic smooth muscle [ 43 ], contributor to the edema that characterizes the CS muscles.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Nevertheless, other organs are also known to be damaged by the virus. [22][23][24][25][26] As for human reproduction, concerns of potential vertical transmission have been raised. 27 Human embryos present all of the machinery needed for SARS-CoV-2 binding, internalization, and replication, suggesting that "in theory" viral infection may compromise embryonic and fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results are controversial. For example, some researchers have reported that SARS-CoV-2 was not detected in the male reproductive tract, [25][26][27][28][29][30][31][32][33][34] while others reported that SARS-CoV-2 RNA was found in the semen or testes of COVID-19 patients. 35,36 There are also unknown factors regarding COVID-19 and male reproduction.Orchitis and broad destruction of the testes were found in deceased COVID-19 patients, 35,37 while the pathological characteristics in survivors remain unknown.…”
mentioning
confidence: 99%